2006
DOI: 10.1088/0964-1726/16/1/006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of the electrical anisotropy in unidirectional carbon-fiber-reinforced polymer composites

Abstract: In this paper, unidirectional CFRP composites are considered as an electrical percolation system, which consists of electrically conductive carbon fibers and electrically nonconductive epoxy resin. Due to the contact behavior of the carbon fibers, CFRP has electrical conductivity in the width direction. Resistance measurements using the DC four-probe and the DC six-probe methods are conducted for the unidirectional CFRP specimens with different fiber volume fractions, i.e. different contact conditions. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 17 publications
1
48
0
Order By: Relevance
“…It is well established that the conductivity of UD CFRP laminates is higher in the 0 • fibre direction than the transverse 90 • direction [4][5][6][7][8].…”
Section: Waveguide Measurement Of Ud Cfrpmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the conductivity of UD CFRP laminates is higher in the 0 • fibre direction than the transverse 90 • direction [4][5][6][7][8].…”
Section: Waveguide Measurement Of Ud Cfrpmentioning
confidence: 99%
“…However, UD laminates possess very poor mechanical properties in all other directions, thus it is considered good design practice to include at least 10% of plies in each of the 45 • , −45 • and 90 • directions. One special case is the QI laminate, referring to The conductivity of the UD CFRP panels has previously been discussed in the literature [3][4][5][6][7][8]. It is reported that the conductivity of UD CFRP panels ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This requires manufacturing of specific samples with unidirectional plies at least for σ x and σ x extraction. To avoid manufacturing of dedicated samples, it is possible to combine measurement results with an analytical model [1][2][3] taking into account of the nonuniform current distribution in the sample in order to obtain the right conductivity in the required direction.…”
Section: Fig 1 "Four Points" Methodsmentioning
confidence: 99%
“…Knowing the electrical conductivity of CFRPs, as well as the other electromagnetic properties, is of great importance for various applications such as electromagnetic compatibility [1], eddy current non-destructive testing [2], induction heating [3], and for some electromechanical applications [4]. Unfortunately, these proprieties are not known in advance; they are determined either by using the homogenization techniques [3], or by appropriate measurements once the material is constructed [5]- [6]. The four points bridge technique has been used to determine the electrical conductivity of CFRPs [5]; however, the high anisotropy and low dimensionality of these materials make this technique in many cases difficult and unreliable [6].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these proprieties are not known in advance; they are determined either by using the homogenization techniques [3], or by appropriate measurements once the material is constructed [5]- [6]. The four points bridge technique has been used to determine the electrical conductivity of CFRPs [5]; however, the high anisotropy and low dimensionality of these materials make this technique in many cases difficult and unreliable [6]. Contactless methods, based on resonant circuits [6] and on the physics of the eddy currents [7], have been proposed to determine the global electrical conductivity of CFRPs; however, the anisotropy has been weakly treated.…”
Section: Introductionmentioning
confidence: 99%